The Involvement of Women’s Instant Politics in the Legislative Candidates From 2019-2024 Base on Gender Justice in Jambi City - Yusnaini Yusnaini; Eraskaita Ginting (Jurnal Komunikasi, 2023)
In the 2019 legislative elections, the issue of women's representation in politics, as much as 30%, is interesting to study. Law No.7 of 2017 in article 245 states that the list of prospective candidates contains at least 30% women. The problem now is the lack of women's interest in politics and the lack of female cadres. Political parties need to find an instant way to make women more than only commodities to fulfill the party's qualification requirements. This study aims to explore the dynamics of women's involvement in legislative nominations in Jambi City and the government's participation in maximizing women's involvement. This research was conducted in Jambi City using a case study approach. The selection of the data was from political party officials and at the same time, they became the research informants. In addition, the General Election Commission (KPU) of the City of Jambi was a supplementary informant. Data collection was done through brainstorming and interviews. This research uses the theory of liberal feminism and the theory of gender politics. Furthermore, this research will find a model of gender equality in politics based on gender justice in terms of representation in the political world by showing partiality to be on the agenda and the issues of women.